COMPARATIVE ANALYSIS OF THE USE OF CONFISCATION AND REQUISITION INSTITUTIONS IN CRIMINAL PROCEEDINGS - Khudaybergenov Baxram Kuanishbaevich (American Journals, 2023)
This article discusses the current problems of criminal procedure law concerning the issue of confiscation and requisition. The seizure of property as a forced reaction of the state to the actions of participants in legal relations is regulated by the norms of various branches of law, such as criminal, civil, administrative and land. The variety of regulatory norms indicates the need for an intersectoral study of compliance with the concepts used in regulatory legal acts and the grounds for the use of confiscation and requisition.
Keywords: criminal procedure, civil law, confiscation of property, requisition, legal instruments, intersectoral regulation, current problems of criminal procedure, blank norms, seizure of property, compensation for harm.